2019
DOI: 10.1186/s40729-019-0163-9
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of atrophic jaw using iliac onlay bone graft combined with dental implants

Abstract: BackgroundRehabilitating severely atrophic alveolar crests remains challenging for implantologists and maxillofacial surgeons. Recently, a combination of augmentation and dental implantation has been used to treat cases with severe bone atrophy in the maxilla and mandible. Among autogenous bone grafts, iliac bone grafting (IBG) is considered safe for collecting large amounts of bone and obtaining high-density multipotent cells. However, vertical bone resorption may occur during the initial healing stage after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 37 publications
0
34
0
1
Order By: Relevance
“…This retrospective study is reported following Strengthening the Reporting of Observational studies in Epidemiology (STROBE) guidelines [ 14 , 15 ]. From May 2013 and February 2015, 61 partially and fully edentulous patients who underwent Stella® implant placement between in the Department of Oral and Maxillofacial Surgery in the Seoul National University Dental Hospital were reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…This retrospective study is reported following Strengthening the Reporting of Observational studies in Epidemiology (STROBE) guidelines [ 14 , 15 ]. From May 2013 and February 2015, 61 partially and fully edentulous patients who underwent Stella® implant placement between in the Department of Oral and Maxillofacial Surgery in the Seoul National University Dental Hospital were reviewed.…”
Section: Methodsmentioning
confidence: 99%
“…Oral rehabilitation with dental implants is a well addressed topic in Dentistry and is considered as the best alternative for the replacement of missing teeth that were lost by many reasons ( 1 ). However, a more careful planning is needed when an atrophic maxilla is rehabilitated, which represents a true challenge for implant dentistry ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, dental implants provide frequently long-term survival compared to conventional prostheses [ 5 ]. The long-term maintenance of implant function and aesthetics are followed; nevertheless, insufficient bone volume would restrict the placement of dental implant with adequate length and width [ 6 ].…”
Section: Introductionmentioning
confidence: 99%